Implementation of differentiated guidance and counseling services at junior high school - Hatmoko, Agus Dwi; Khasanah, Ratna Hidayati; Handaka, Irvan Budhi (International Journal on Education Insight, 2023)
This research aims to determine the implementation of differentiated guidance and counseling services at SMP Muhammadiyah 3 Yogyakarta, one of private junior high schools in Yogyakarta, Indonesia. This research was carried out by taking a sample of 4 classes, namely 8a, 8b, 8c, and 8d. The methods used in this research are observation and study literature to strengthen the research argument. Apart from that, we also used a qualitative descriptive approach in answering the questions in this research. SMP Muhammadiyah 3 Yogyakarta implements differentiated guidance and counseling services by distributing questionnaires to determine students’ learning needs and characteristics. From the results of the questionnaire, a service implementation plan was prepared as a guideline for implementing guidance and counseling services in the classroom.